Polyphenolic tea catechins : health promotion, disease prevention and molecular mechanisms of action - Umar, Kabir Mustapha; Mohammed, Abdulkarim Sabo; Abdul Hamid, Azizah; Saari, Nazamid; Radu, Son (Nova Science Publishers, 2012)
It is well documented that most natural products are enriched with bio-active components that have protective action. There is currently a growing body of evidence that supplementing the human diet with natural products is of major benefit for human health and well-being. Nowadays, the use of complementary/alternative medicine, functional food and especially the consumption of natural products have been increasing rapidly worldwide, mostly because of the supposedly less frequent side effects. Both in conventional and traditional medicines, natural products continue to provide valuable therapeutic agents. The issues regarding the efficacy and safety of currently available modern medicine agents have prompted the search for safer and more effective alternatives. This book focuses on implications of traditional and processed foods for health and disease prevention.